Exploring Indian wheat genotypes for less Celiac disease toxic epitopes - Narwal, Sneh; Sharma, Bunty; saini, Ritu; Singh, Ram Baran; Gupta, Om Prakash; Pandey, Vanita; Ram, Sewa; Singh, Gyanendra Pratap (Journal of Cereal Research, 2025)
The conflicting results on the immunogenicity of ancientand modern wheat varieties highlights the need toscreen the large wheat germplasm available includingdifferent wheat species, wild relatives and synthetics.The identified genotypes with low CD toxicity can beused in breeding programmes for reducing CD toxicepitopes in high yielding varieties. This study is a verysmall initiative where only one monoclonal antibodyagainst few epitopes has been used. More monoclonalantibodies can be used in future studiesto target moreCD toxic epitopes.The most important challenge whiledeveloping a new genotype with low CD toxicity eitherby breeding or genetic engineering will be to keep thebaking and processing quality of the wheat intact.Thiswill bring less CD toxic wheat products in food chain withconsequences of reduced celiac diseaseDOI.10.25174/2582-2675/2020/89975